mortalitet PREDICTORS OF TREATMENT OUTCOME OF SURGICAL PATIENTS IN THE INTENSIVE CARE UNIT: LITERATURE REVIEW - Bogdanović Vasić, Slobodanka; Joković , Dragan; Pavić, Katarina; Antonić , Roland; Arandjelović, Branimirka; Savić, Nikola (HEALTH CARE, 2025)
Intensive care involves the care of life-threatening patients, i.e. care of critically ill patients who need intensive monitoring, treatment and care in order to maintain hemodynamic and respiratory balance, in order to reduce the number of complications and deaths. The aging of the population, the increased complexity of care, as well as the increasingly diverse pathology and symptomatology of certain diseases and conditions, influence the increase in the need for intensive care services in all branches of medicine, primarily in surgery. The aim of this review is to identify predictors of treatment outcomes for surgical patients in intensive care units (ICUs). Data were collected by searching several databases: PubMed, Google Scholar, Web of Science and Embase. A search was conducted for the past twenty years using the following keywords: intensive care unit, surgery, predictors, and treatment outcome. Included in our analysis were papers that analyzed the clinical outcomes of surgical patients who stayed in the ICU. It is observed that the predictors of the outcome of the treatment of surgical patients in ICU are: the severity of the patient’s clinical picture before hospitalization, the type and scope of the operation, age, obesity, number of comorbidities, postoperative complications, but also the degree of organization of the health service and the competence of the health staff. Therefore, at the local, regional and global level, continuous monitoring and evaluation of predictors of treatment outcomes for surgical patients in the ICU should be developed, bearing in mind that life-threatening patients are hospitalized and that there is a high risk of complications and death. By identifying the predictors of the outcome of the treatment of surgical patients in the ICU, it will contribute to the adoption of strategies to improve the treatment of these patients.